2015
DOI: 10.1021/jm501258m
|View full text |Cite|
|
Sign up to set email alerts
|

Structure-Guided Design of a Series of MCL-1 Inhibitors with High Affinity and Selectivity

Abstract: Myeloid cell leukemia 1 (MCL-1) is a BCL-2 family protein that has been implicated in the progression and survival of multiple tumor types. Herein we report a series of MCL-1 inhibitors that emanated from a high throughput screening (HTS) hit and progressed via iterative cycles of structure-guided design. Advanced compounds from this series exhibited subnanomolar affinity for MCL-1 and excellent selectivity over other BCL-2 family proteins as well as multiple kinases and GPCRs. In a MCL-1 dependent human tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 39 publications
4
122
1
1
Order By: Relevance
“…Where indicated, cells were pretreated for 60 minutes with z-VADfmk (ICN). Navitoclax and A-1210477 were synthesized as described previously (28,29). Unless otherwise indicated, all chemical reagents were obtained from Sigma-Aldrich.…”
Section: Reagents Cell Culture and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Where indicated, cells were pretreated for 60 minutes with z-VADfmk (ICN). Navitoclax and A-1210477 were synthesized as described previously (28,29). Unless otherwise indicated, all chemical reagents were obtained from Sigma-Aldrich.…”
Section: Reagents Cell Culture and Treatmentmentioning
confidence: 99%
“…It is, therefore, of considerable therapeutic interest to inhibit the expression and/or function of MCL-1 in cancer and in particular, breast cancer. We recently described the synthesis of small molecules that selectively inhibit MCL-1 function (28). Here, we describe the identification of breast cancer cell lines that are addicted to the oncogene MCL-1, evaluate the mechanism of cell death resulting from selective loss of MCL-1 function, and discuss the consequences for breast cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulties of this challenge, a series of MCL-1 inhibitors derived from indole-2-carboxilic acid has been obtained by high-throughput screening and structure-guided design. 37 The compounds bind to MCL-1 with excellent high affinity (0.45 nM) and selectivity over other prosurvival BCL-2 family proteins. A mechanistic study has shown that the lead compound A-1210477 and related analogs can disrupt the interactions of MCL-1 with BIM and NOXA, penetrate living cells, and act via an on-target mechanism.…”
Section: Discovery Of Novel Bh3 Mimeticsmentioning
confidence: 99%
“…Concerns over the Fmoc protecting group were considered, but as these compounds are primarily meant as chemical probes or potential leads, further development may discover more effective alternatives. Indeed, the Fmoc group is somewhat reminiscent of structural features present in Souers’ A‐121047716d and Fesik's 2‐indole‐acylsulfonamides,20 which are highly potent and selective Mcl‐1 binders. Interestingly, the most potent small molecules did not result from the combination of the most potent small‐molecule peptide hybrids 2 and 9 , as might be expected.…”
mentioning
confidence: 99%
“…Two compounds, 18 and 21 , were ineffective against AsPC‐1 cells at the concentrations evaluated in our assay, which may suggest that they are acting through the inhibition of Mcl‐1. The difference in the magnitude of activity in cells compared to the in vitro FA assay is a commonly observed phenomenon, and largely due to cell permeability 16d, 23. Indeed, some of the more potent compounds in the FA assay showed no activity in the cellular assays, such as compound 17 (IC 50 =102±14 n m ), suggesting an inability to cross the cell membrane.…”
mentioning
confidence: 99%